(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Although encryption is used to protect data from being read by unintended recipients it still does not ensure complete safeness. The reason being that information can be gathered by an eavesdropper by indirect inferences like packet classification and traffic analysis. Thus our aim is to protect the header from being read by selective insider jammers. In such a scenario where we have a selective insider jammer who is active only for a period of time, protecting the header information should be given higher priority as these adversaries classify the packets using first few bits from the header fields and add bit errors to the packet if it is an important one. Header information can be protected using modified anonymous routing scheme where we employ multiple level of encryption of the packet to prevent the adversary from classifying the packet using the header information.